Enzyme-mediated ligation technologies for peptides and proteins. (June 2017) - Schmidt, Marcel; Toplak, Ana; Quaedflieg, Peter JLM; Nuijens, Timo
Highlights: Enzymatic ligation offers a powerful toolbox for site-selective protein labelling. Enzymatic ligation facilitates access to complex protein architectures. Enzymatic ligation effectively complements chemical ligation strategies. CEPS bears great potential for the production of pharmaceutical peptides Abstract : With the steadily increasing complexity and quantity requirements for peptides in industry and academia, the efficient and site-selective ligation of peptides and proteins represents a highly desirable goal. Within this context, enzyme-mediated ligation technologies for peptides and proteins have attracted great interest in recent years as they represent an extremely powerful extension to the scope of chemical methodologies ( e.g. native chemical ligation) in basic and applied research. Compared to chemical ligation methods, enzymatic strategies using ligases such as sortase, butelase, peptiligase or omniligase generally feature excellent chemoselectivity, therefore making them valuable tools for protein and peptide chemists.